2018
DOI: 10.4168/aair.2018.10.4.287
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Necessity to Prescribe Consumption of Walnuts Cooked by Different Processing Techniques to Patients With Walnut Allergy?

Abstract: The present study focused on identifying the usual methods of cooking walnuts in order to investigate changes in walnut allergen activity caused by cooking and evaluated the allergenic changes in walnut proteins within raw, dry-fried and boiled walnuts. Previous studies have reported a decrease in the allergen activity of walnut by thermal processing methods, which are not used in Korean kitchens, such as dry-frying and boiling. In Korea, Walnuts are consumed with rice and usually boiled and stir-fried with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, some scholars also have found that foods could cause a variety of diseases after dry-fried or high-temperature processed. Oh et al [ 48 ] revealed that the allergen activity of raw, dry-fried, and boiled walnuts differed, and the walnut allergen activity was reduced by thermal processing methods. Several studies have revealed that nutrient-sensing mechanisms existed in the gastrointestinal tract and resulted in the transmission of neuronal signals to the brain, particularly satiety[ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some scholars also have found that foods could cause a variety of diseases after dry-fried or high-temperature processed. Oh et al [ 48 ] revealed that the allergen activity of raw, dry-fried, and boiled walnuts differed, and the walnut allergen activity was reduced by thermal processing methods. Several studies have revealed that nutrient-sensing mechanisms existed in the gastrointestinal tract and resulted in the transmission of neuronal signals to the brain, particularly satiety[ 49 ].…”
Section: Discussionmentioning
confidence: 99%